Energy absorbers on the steel plate – rubber laminate after deformable projectile impact - Purwanto, Helmy; Soenoko, Rudy; Purnowidodo, Anindito; Suprapto, Agus (Eastern-European Journal of Enterprise Technologies, 2018)
The ability of energy absorption can be used to measure the strength of material against ballistic impact. This paper aims to analyze the rubber plated energy absorption plate that was shot with deformable projectiles. This study was conducted using numerical simulations based on the finite element that have been verified with experimental results. The simulation setting on a steel plate with different hardness with the addition of rubber thickness is prepared as a ballistic test panel. Manufacturing between layers made non fix with the back plate. Panel shot by using 5.56x 45 mm deformable caliber bullet with a distance of 15 m of normal attack angle. The finite element code with Johnson-Cook and Mooney-Rivlin elasto-plastic material models was were employed to perform the simulation study. Simulation results show the energy due to ballistic impact received and absorbed by the panel rises significantly shortly after the collision until reaching a certain number on a single plate where energy will decrease because the projectile successfully penetrated the plate. While on a layered plate, after the projectile succeeded in penetrating the front side plate, the absorption energy reached the maximum number and then remained constant, which caused the projectile not to be able to penetrate the next layer. These findings indicate that the addition of rubber with a layered structure is able to absorb the energy of ballistic impact